Internationalization in the context of academic capitalism. (March 2020) - Appe, Susan
This article is written from the perspective of a faculty member in a professional graduate degree program who is committed to internationalization, but also notes its challenges given the context in which higher education finds itself. First, the article outlines the ways in which higher education is thinking about internationalization, in particular with a focus on faculty-led short-term study abroad programs. Second, the article juxtaposes internationalization with the current conversation and debates about academic capitalism. Finally, it ends with overarching topics that deserve further exploration and include: (a) that internationalization is often tailored to faculty interests but that this might make systemic assessment challenging; (b) that there are shifting relations among the university central offices related to internationalization processes and academic departments; and (c) given the academic capitalism debates, the article asks whether we can implement and assess our internationalization processes while still adhering to academic quality and credibility.